New Insights on the Mechanism of Interaction Between Light (bio) Alcohols and Metallic Mixed Oxides Catalysts - Velasquez Ochoa, Juliana <1984> (Alma Mater Studiorum - Università di Bologna, 2016)
This research intends to explore the mechanism behind the transformation of ethanol over basic and acid/base catalysts. The approach used was first to explore in depth the role of the MgO which is a common component of both reactions (Lebedev and Guerbet) and then to study the incorporation of Si ion and the effect on the acid/base properties of the resulting materials. Moreover, the addition of a dopant with acid/dehydrogenating properties was also explored. Further on, several catalysts were tested under the usual conditions for this reaction and characterization was made in order to understand their particular behavior. An important tool in this research was the in-situ infrared diffuse reflectance spectroscopy (DRIFTS) coupled with mass spectrometry (MS) due to the possibility that it offers to study what occurs on the catalysts surface under real working conditions. This study allowed to gain new insights on the mechanism behind the catalytic upgrading of ethanol on basic and acid/base mixed oxides, giving an alternative view of the mechanism for the Lebedev and Guerbet reactions that permitted us to discard the key role of the generally accepted intermediates and helped to explain several experimental findings not clear before.